2015
DOI: 10.1111/tpj.13090
|View full text |Cite
|
Sign up to set email alerts
|

A highly specific microRNA‐mediated mechanism silences LTR retrotransposons of strawberry

Abstract: SUMMARYSmall RNAs are involved in a plethora of functions in plant genomes. In general, transcriptional gene silencing is mediated by 24-nucleotide siRNAs and is required for maintaining transposable elements in a silenced state. However, microRNAs are not commonly associated with transposon silencing. In this study, we performed small RNA transcriptome and degradome analyses of the Rosaceae model plant Fragaria vesca (the woodland strawberry) at the genome-wide level, and identified miRNA families and their t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 54 publications
(83 reference statements)
0
20
0
Order By: Relevance
“…Mutations in a subunit of RNaseP (involved in the processing of the 5΄ trailer of tRNA precursors) in Drosophila leads to sterility due to activation of DNA damage checkpoint proteins and TE reactivation coupled with piRNA source collapse ( 43 ). Moreover, two miRNAs (miR1511 and miR845, known to target LTR retrotransposons) ( 44 ) have precursors that have an evolutionary origin in the tRNA MetCAT ( 45 ). Interestingly, here we found that the tRNA MetCAT by itself produces a 19 nt tRF-5 that directly targets the LTR retrotransposon Athila6A .…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in a subunit of RNaseP (involved in the processing of the 5΄ trailer of tRNA precursors) in Drosophila leads to sterility due to activation of DNA damage checkpoint proteins and TE reactivation coupled with piRNA source collapse ( 43 ). Moreover, two miRNAs (miR1511 and miR845, known to target LTR retrotransposons) ( 44 ) have precursors that have an evolutionary origin in the tRNA MetCAT ( 45 ). Interestingly, here we found that the tRNA MetCAT by itself produces a 19 nt tRF-5 that directly targets the LTR retrotransposon Athila6A .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, high-throughput sequencing technology resulted in a sharp increase in the magnitude of genome information and gene expression profiles. Many studies have shown that miRNAs possess important regulatory roles in the process of fruit development and ripening (Zeng et al, 2015; Šurbanovski et al, 2016). Firstly, several expression profile studies indicated that numerous miRNAs are exclusively or preferentially expressed in fruits (Liu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the preprocessing of DGE datasets, filtering out singleton reads is frequently included [4648]. For the sRNA module, screening out reads based on alignment with noncoding RNA databases (such as tRNA, rRNA, and snoRNA) [49, 50] is under development. Adding statistics such as per-read quality distribution and length distribution is also worth consideration.…”
Section: Discussionmentioning
confidence: 99%